Chromatographic and mass spectrometric analysis of secondary metabolites of Deschampsia antarctica from Galindez Island, Argentine Islands - Ivannikov, Roman; Anishchenko, Viktor; Kuzema, Pavlo; Stavinskaya, Oksana; Laguta, Iryna; Poronnik, Oksana; Parnikoza, Ivan (Polish Polar Research, 2022)
The aim of this work was to study the polyphenolic composition of Deschampsia antarctica É. Desv. plants grown in natural conditions at different locations on the Galindez Island, Argentine Islands, the maritime Antarctic. The plants were collected during the summer season of the 26th Ukrainian Antarctic Expedition (2020–2022). The extracts of 21 plants were obtained and the composition of the extracts was analyzed by means of high-performance liquid chromatography and matrix-assisted laser desorption/ionization mass spectrometry. The antioxidant properties of the extracts were characterized using the DPPH (2,2-diphenyl-1-picrylhydrazyl) test. The extracts contained large amount of polyphenolic compounds, with flavonoids and phenolic acids, as well as their derivatives, being the most common classes of the phenols. Using the HPLC data the content of various phenols in the plants was systematic studied. It has been found that in all plants the most abundant phenols were flavonoids/flavonoid derivatives (on average about 75% of total mass of phenols). Among the flavonoids, luteolin derivatives predominated (86–94% of the total mass of flavonoids), and, among luteolin derivatives, the main compounds were orientin, orientin 2"-O-β-arabinopyranoside and isoswertiajaponin 2"-O-β-arabinopyranoside (67–83% of the total mass of luteolin derivatives). It has been also found that all the extracts had high activity in inhibition of DPPH radicals and that the antioxidant activity of the extracts correlated with total content of phenols in the samples. Thus, Deschampsia antarctica É. Desv. plants are a valuable source of natural phenolic antioxidants, and the most common antioxidants in the extracts are orientin, orientin 2"-O-β-arabinopyranoside and isoswertiajaponin 2"-O-β-arabinopyranoside.